Compensating human subjects providing oocytes for stem cell research: 9-year experience and outcomes - Zakarin Safier, L.; Gumer, A.; Kline, M.; Egli, D.; Sauer, M. V. (Journal of assisted reproduction and genetics, 2018)
Purpose Human oocytes are arguably one of the most important cell types in humans, yet they are one of the least investigated cells. Because oocytes are limited in number, the use of high-quality oocytes is almost entirely in reproduction. Furthermore, regulatory hurdles for research on gametes and regulations on funding related to research on gametes present significant obstacles to research and the advancement of reproductive treatments. Here we report the outcomes of the largest compensated oocyte donation program for research in the USA to date, and probably worldwide. Methods Women who participated in oocyte donation for research between 2008 and 2017 were contacted in a phone interview and completed a standardized questionnaire. Results Of 114 participants, 98 oocyte donors completed donation, donating 1787 mature MII oocytes and a total of 86 skin biopsies. Complication rate, including minor complications, of oocyte donation was 8/98, or 8.1%, for which two involved follow-up. Fifty-seven donors answered questions about their experience. Participants were incentivized primarily by money and a desire to help others and reported an overall favorable experience. Most, but not all, human subjects recalled that they had donated for research, and approximately half recalled that their oocytes were being used specifically for stem cell research. Conclusions Compensated oocyte donation provides a reliable path to obtaining high-quality oocytes for research and is reviewed favorably by oocyte donors. The continuation of programs that offer compensation for oocyte donation is invaluable to continued progress and advancements in stem cell research and human embryology, and for the advancement of novel reproductive treatments.